China-ASEAN Criminal Justice Cooperation Based on Value Consensus in the Context of the Belt and Road Initiative - Xinming, Wen; Basir, Salawati Mat; Rahman, Nurul Hidayat Ab (Jurnal Cita Hukum, 2026)
Against the background of the Belt and Road Initiative (BRI) and the increasing complexity of transnational crime, criminal judicial cooperation has become an essential yet insufficiently examined aspect of China–ASEAN legal cooperation. Existing BRI scholarship has primarily focused on investment protection and commercial dispute resolution, leaving the normative foundations of criminal judicial cooperation largely underexplored. This article adopts a value-based analytical framework to examine the feasibility of criminal judicial cooperation between China and ASEAN states. Through an analysis of ASEAN criminal judicial cooperation instruments and practices, the article identifies core value orientations embedded in ASEAN mechanisms, including the prioritisation of state sovereignty and legal autonomy, a functional emphasis on public order and regional security, minimum guarantees of procedural justice, and a constrained pursuit of cooperation efficiency. These value orientations are then compared with those reflected in China’s criminal justice system. The analysis demonstrates that, despite differences in legal traditions and institutional structures, China and ASEAN share a substantial overlap at the level of value prioritisation and normative bottom lines. The coexistence of diverse legal traditions, including Islamic law influences within ASEAN, further illustrates the viability of cooperation based on minimum value consensus rather than legal uniformity. Building on this finding, the article proposes a value-consensus-oriented model for China–ASEAN criminal judicial cooperation that balances effectiveness, legal diversity, and state sovereignty.